Catalogue of Best Practices in Citizen Journalism: From citizen journalism to the platformization of news - Crespo, M.; Álvares, Cláudia; Cardoso, G.; Moreno, J.; Sepúlveda, R.; Foà, C. (2022)
The goals of this report are threefold: to try to understand how citizens interact with journalism in Europe, to try to categorize those interactions and to present a list of cases from different countries which can be considered as examples of best practices. To do so, we present a brief contextualization of journalism and citizen journalism, and a conceptual approach to three major categories of interaction, practices, and the use/reuse of journalistic content by citizens. We have taken as our starting point citizens’ engagement with journalism as both product and content: citizens collaborate with journalists in content production, citizens emulate journalistic practices, and citizens use/reuse journalism to contribute to public discourse and democracy. The report further develops a synoptic analysis of professional and user-generated news contents, so as to provide us with a better understanding of the potentialities, limits, and reliability of so-called citizen journalism. A selection of positive cases is expounded on, aiming to be brought to the attention of policymakers.